HIV incidence in a multinational cohort of men and transgender women who have sex with men in sub-Saharan Africa: Findings from HPTN 075 - Sandfort, TGM; Mbilizi, Y; Sanders, EJ; Guo, X; Cummings, V; Hamilton, EL; Akelo, V; Panchia, R; Dominguez, K; Stirratt, MJ; Chege, W; Lucas, J; et al. (Public Library of Science, 2021)
Few studies have assessed HIV incidence in men who have sex with men (MSM) and transgender women (TGW) in sub-Saharan Africa (SSA). We assessed HIV incidence and its correlates among MSM and TGW in SSA enrolled in the prospective, multi-country HIV Prevention Trials Network (HPTN) 075 study, conducted from 2015 to 2017. Participants were enrolled at four sites in SSA (Kisumu, Kenya; Blantyre, Malawi; Cape Town and Soweto, South Africa). Eligible participants reported male sex assignment at birth, were 18 to 44 years of age, and had engaged in anal intercourse with a man in the preceding three months. Participation involved five study visits over 12 months. Visits included behavioral assessments and testing for HIV and sexually transmitted infections. Twenty-one of 329 persons acquired HIV during the study [incidence rate: 6.96/100 person-years (PY) (95% CI: 4.3, 10.6)]. Among TGW, HIV incidence was estimated to be 8.4/100 PY (95% CI: 2.3, 21.5). Four participants were found to have acute HIV infection at their first HIV-positive visit. HIV incidence varied among the four study sites, ranging from 1.3/100 PY to 14.4/100 PY. In multivariate longitudinal analysis, factors significantly associated with HIV acquisition were engagement in unprotected receptive anal intercourse [adjusted hazard ratio (AHR) 5.8, 95% confidence interval (CI): 2.4, 14.4] and incident rectal gonorrhea and/or chlamydia (AHR: 2.7, 95% CI: 1.1, 6.8). The higher HIV incidence in Cape Town compared to Blantyre could be explained by the higher prevalence of several risk factors for HIV infection among participants in Cape Town. Annual HIV incidence observed in this study is substantially higher than reported HIV incidence in the general populations in the respective countries and among MSM in the United States. Intensification of HIV prevention efforts for MSM and TGW in SSA is urgently needed.